Rapid Preparation of Spherical Granules via the Melt Centrifugal Atomization Technique - Yan Yang; Nan Zheng; Xiaoyue Wang; Ryan Ivone; Weiguang Shan; Jie Shen (MDPI AG, 2019)
Granules with superior fluidity and low moisture absorption are ideal for tableting and capsule filling. Melt granulation as a solvent-free technology has attracted increasing interest for the granulation of moisture-sensitive drugs. The objective of the present study was to develop a solvent-less and high throughput melt granulation method via the melt centrifugal atomization (MCA) technique. The granule formability of various drugs and excipients via MCA and their dissolution properties were studied. It was found that the yield, fluidity, and moisture resistance of the granules were affected by the drug and excipient types, operation temperature, and collector diameter. The drugs were in an amorphous state in pure drug granules, or were highly dispersed in excipients as solid dispersions. The granules produced via MCA showed an improved drug dissolution. The present study demonstrated that the solvent-free, one-step, and high-throughput MCA approach can be used to produce spherical granules with superior fluidity and immediate drug release characteristics for poorly water-soluble and moisture-sensitive therapeutics.